Case Report: Anesthetic Management of Cesarean Section in a Patient With Paraplegia - Su, Yongchun; Lei, Xiaofeng; Yu, Jin (Frontiers in Medicine, 2022)
Background With the advancement of medical science and rehabilitative care, more women with spinal cord injury (SCI) can conceive. However, autonomic hyperreflexia due to SCI complicates anesthesia management during cesarean sections. Case Presentation This study reports the anesthesia management in a woman with paraplegia with a T6 SCI lesion who underwent a cesarean section. It also reviews the anesthesia strategies used in other studies. Spinal anesthesia with a low concentration of ropivacaine was administered along with dexmedetomidine for sedation. Stable hemodynamics were achieved without complications. Conclusions Based on the reported case and literature review, we conclude that the intrathecal block is the preferred choice for women with paraplegia who require cesarean section if the lumbar bone structure allows puncture attempts.